DEEP-LEVEL GEODYNAMICS: BOUNDARIES OF THE PROCESS ACCORDING TO GEOCHEMIC AND PETROLOGIC DATA - Alexei V. Ivanov (Геодинамика и тектонофизика)
Geochemical features for volcanic rocks and petrologic data for deep-seated inclusions, which can be used to infer mass transfer between different geospheres, are reviewed. It is typically believed that slabs can subduct as deep as the core-mantle boundary with the following recycling by plumes coming up to the sublithospheric regions of magma generation. However, the petrologic evidence of the deepest accessible material is limited by the depth of the uppermost lower mantle (~650–700km), i.e. by the depth of the deepest earthquakes. Ferropericlase inclusions in some diamonds do not exclude involvement of deeper mantle horizons, yet do not unambiguously support it. No unambiguous confirmation of involvement of the lower mantle into magma generation underneath volcanically active regions is obtained from geochemical data either, while the geochemical data suggest complete chemical isolation of the Earth’s core from the upper mantle processes.